Relationship Between Caregiver Loads with Family Interaction Pattern with Mental Disorder at Home - Nababan, Yosevin Karunia; Yusuf, Ah; Nimah, Lailatun (Universitas Airlangga, 2019)
Introduction: Families as caregivers their family with mental disorder experience the burden of physical, emotional and financial disturbances due to the patient's abnormal behavior, social dysfunction and inability to support themselves. Due to the burden they experience, caregivers show symptoms of high stress and anxiety to affect patterns of interaction.Method: The design of this study was cross sectional. A sample of 123 family sufferers of mental disorder member who visited the mental health polyclinic at the Menur General Hospital in Surabaya was obtained using a consistent sampling technique. Data were obtained from the Zarit Caregiver Burden Questionaire and the interaction pattern questionnaire was then analyzed using the Spearman Rho correlation test.Results: The results showed that there was a significant relationship between the burden of caregiving with interaction patterns (p = 0.032) at a significance value <0.05. The correlation coefficient r = -0,194. This shows that there is a low relationship with a negative direction, so that the higher the burden of caregiving is felt the lower the interaction patterns experienced by family caregivers of people with mental disorder.Conclusion: There is a significant relationship between caregiving burden with the negative caregiver interaction patterns of mental disorder sufferers' families, which means that the higher the caregiver burden felt by caregivers, the lower the interaction patterns.